Literasi Digital Masyarakat Pedesaan: Studi di Desa Tanah Tinggi Kabupaten Batubara - Trisna, Nabilla Fairus Izzati Eka; Batubara, Abdul Karim (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
The development of information and communication technology has brought significant changes in people's lives, including in rural areas. However, varying levels of digital literacy are an important factor in determining how people can optimally utilize the internet. This study examines the level of digital literacy of the community in Tanah Tinggi Village, Batubara District, and how they utilize the internet in their daily activities. The method used is descriptive qualitative with interviews as the data collection technique, using purposive sampling to select appropriate and relevant informants. The research findings show that most Tanah Tinggi villagers have utilized the internet for various needs, such as communication, entertainment, education, and economic activities. However, the community's level of digital literacy is still moderate. They are quite active in accessing and using information from the internet, but their ability to critically evaluate and verify information is still limited. This can be seen from the difficulty in recognizing and counteracting fake news or hoaxes that are widely circulated on social media. This study emphasizes the importance of improving digital literacy so that people are not only active users of the internet, but also able to use information wisely and critically for optimal benefits in their daily lives.